An empirical analysis of electricity consumption in Cyprus - Zachariadis, Theodoros; Pashourtidou, Nicoletta (My University, 2007)
The paper presents the first empirical analysis of electricity consumption in Cyprus. Using annual data from 1960 to 2004, we have examined electricity use in the residential and the services sectors, which are the fastest-growing electricity consumers in the island, and its interaction with income, prices and the weather. The analysis was performed with the aid of time series analysis techniques such as unit root tests with and without a structural break in levels, cointegration tests, Vector Error Correction models, Granger causality tests and impulse response functions. Results show long-term elasticities of electricity use above unity for income, and of the order of − 0.3 to − 0.4 for prices. In the short-term electricity consumption is rather inelastic, mostly affected by weather fluctuations. Granger causality tests confirm exogeneity of electricity prices and bidirectional causality between residential electricity consumption and private income. The commercial sector is less elastic and reverts faster to equilibrium than the residential sector. Despite the relatively small sample size, results reported here are quite robust and can be used for forecasts and policy analyses.
Keywords: Unit root; Structural break; Cointegration; Granger causality; Impulse response